Regulatory role of KCa3.1 in immune cell function and its emerging association with rheumatoid arthritis - Lin, Yi; Zhao, Ying-Jie; Zhang, Hai-Lin; Hao, Wen-Juan; Zhu, Ren-Di; Wang, Yan; Hu, Wei; Zhou, Ren-Peng (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a common autoimmune disease accompanied by chronic inflammation. Immune dysfunction is an essential mechanism in the pathogenesis of rheumatoid arthritis and directly linked to synovial inflammation and cartilage/bone destruction. Intermediate conductance Ca2+-activated K+ channel (KCa3.1) is considered a significant regulator of proliferation, differentiation, and migration of immune cells by mediating calcium signal transduction. Earlier studies have demonstrated abnormal activation of KCa3.1 in the peripheral blood and articular synovium of RA patients. Moreover, knockout of KCa3.1 reduced the severity of synovial inflammation and cartilage damage to a significant extent in a mouse collagen antibody-induced arthritis (CAIA) model. Accumulating evidence implicates KCa3.1 as a potential therapeutic target for RA. Here, we provide an overview of the KCa3.1 channel and its pharmacological properties, discuss the significance of KCa3.1 in immune cells, and highlight its emerging role in pathological progression of RA and feasibility as a drug target for modulating the immune balance.